2012
DOI: 10.1007/s10880-012-9322-3
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Psychosocial Factors in Complex Regional Pain Syndrome

Abstract: Complex regional pain syndrome (CRPS) is a disabling pain condition poorly understood by medical professionals. Because CRPS is particularly enigmatic, and has significant impact on patient function, researchers have examined psychological processes present among patients with this diagnosis. This systematic review examines psychosocial factors associated with CRPS, both predictors and sequelae. Our conclusions are that CRPS is associated with negative outcomes, both psychological (e.g., increased depression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 35 publications
1
57
0
8
Order By: Relevance
“…Proposed mechanisms include cortical change and reorganization. Psychological factors, such as depression and anxiety, may be premorbid or occur in response to pain; addressing these components is an important part of managing the disorder [111,112]. …”
Section: Common Post-stroke Pain Subtypesmentioning
confidence: 99%
“…Proposed mechanisms include cortical change and reorganization. Psychological factors, such as depression and anxiety, may be premorbid or occur in response to pain; addressing these components is an important part of managing the disorder [111,112]. …”
Section: Common Post-stroke Pain Subtypesmentioning
confidence: 99%
“…8,9 More broadly, a recent meta-analysis of 24 separate studies on cognition in pain patients concluded that there was a consistent moderate effect of pain on working memory. 10 In a related study, it was observed that approximately 20% of the new patients to a multidisciplinary pain center showed clinically significant impairment on neurocognitive testing.…”
Section: Introductionmentioning
confidence: 99%
“…low-back pain, arthrosis) and limb immobilisation (Marinus 2011) may increase the risk of its development. Psychological traits, such as depression, anxiety, neuroticism and anger, have so far been discounted as risk factors for the development of CRPS : Lohnberg 2013, although further prospective studies are required to substantiate this assertion .…”
Section: Background Description Of the Conditionmentioning
confidence: 99%
“…People with CRPS experience significant suffering and disability (Bruehl 2010;Lohnberg 2013). Preliminary data suggest that interference with activities of daily living, sleep, work and recreation is common and further contributes to a diminished quality of life (Galer 2000;Geertzen 1998;Kemler 2000;Sharma 2009).…”
Section: Background Description Of the Conditionmentioning
confidence: 99%